Digital Competence of Future English Language Teachers: Influence of Age and Gender on Their Self-perception - Mosquera Gende, Ingrid (Forum for Linguistic Studies, 2024)
This research analyses how age and gender may influence the self-perception of prospective secondary school teachers regarding their digital competence in teaching. Testing students’ self-perception can be a starting point for implementing programmes to improve this competence. To this end, the author presents the results of a didactic experience carried out within the framework of the subject Didactics of the English Language, as part of the Master’s Degree in Teacher Training for Compulsory Secondary Education and Baccalaureate, Vocational Training and Language Teaching at a Spanish online university. Therefore, the subjects of the present study are future English teachers who are studying via a distance-learning modality. In order to measure their self-perception, they answered a questionnaire at the beginning and at the end of the course. This is a subject in which the teacher introduces numerous digital tools, both in synchronous online classes and through asynchronous activities, with students’ future teaching practice in mind. A mixed methodology is used: a previously validated quantitative questionnaire and a qualitative analysis of the responses obtained by students in the subject forums. Once the intervention had been carried out and the data analysed, it could be seen that the students’ self-perception in relation to their digital competence decreased, as they became more aware of how many tools they were unfamiliar with before starting the course. However, the difference was not equal between men and women, with the former being more positive than the latter. In reference to age, older participants show, as in the case of women, a greater degree of self-reflection and self-demand. It is expected that these results will be the starting point to try to improve these aspects, taking them into consideration in our classrooms and in our teacher training programs.
Keywords: english; ICT; online education; self-perception; teacher digital competence; teacher training; university